Retirement village buying intention: a case study on the Muslim and non-Muslim Malaysian elderly - Ng, Siew Imm; Fang, Zhao; Lim, Xin Jean; Kamal Basha, Norazlyn; Sambasivan, Murali (Emerald, 2020)
Purpose: The well-being of the elderly is a growing issue of concern for countries around the world. One way to enhance the elderly well-being is to provide housing options suitable to their needs and lifestyle. Retirement village is an accommodation concept foreign to the Malaysian population. Therefore, the purpose of this paper is to bridge this literature gap by analyzing factors that may inhibit or motivate the buying intention of a retirement village unit among the elderly in Malaysia. Design/methodology/approach: Data were collected from 261 Malaysian elderly and analyzed using structural equation modeling PLS. Findings: The results indicated that attitude, subjective norm, perceived behavioral control and social sustainability were significant predictors that explained elderly buying intention of retirement village. Originality/value: The study also found a significant moderating role of religion in attitude–intention relationship. The paper concludes with the study’s implications, limitations and recommendations for future research.